Nanostructured material from hydroxyethyl cellulose for skin tissue engineering - Zulkifli, Farah Hanani; Jahir Hussain, Fathima Shahitha; Abdull Rasad, Mohammad Syaiful Bahari; Mohd Yusoff, Mashitah (Elsevier Ltd., 2014)
tIn this study, a novel fibrous membrane of hydroxyethyl cellulose (HEC)/poly(vinyl alcohol) blend wassuccessfully fabricated by electrospinning technique and characterized. The concentration of HEC (5%)with PVA (15%) was optimized, blended in different ratios (30–50%) and electrospun to get smoothnanofibers. Nanofibrous membranes were made water insoluble by chemically cross-linking by glu-taraldehyde and used as scaffolds for the skin tissue engineering. The microstructure, morphology,mechanical and thermal properties of the blended HEC/PVA nanofibrous scaffolds were characterized byscanning electron microscope, Fourier transform infrared spectroscopy, differential scanning colorime-try, universal testing machine and thermogravimetric analysis. Cytotoxicity studies on these nanofibrousscaffolds were carried out using human melanoma cells by the MTT assays. The cells were able to attachand spread in the nanofibrous scaffolds as shown by the SEM images. These preliminary results showthat these nanofibrous scaffolds that supports cell adhesion and proliferation is promising for skin tissueengineering.